The Impact of Teaching English Literature on improving EFL University Learners’ Performance. - Abdulla Shafiq, Jinan; Zaid, Reem Khalaf (Technium Education and Humanities, 2024)
Teaching English Literature is important in learning English language in Uinversities. In all the English departments in Universities, having an English literature course is a must. Generally speaking, literature has a huge role in enhancing the student’s ability in the four skills of learning language. Therefore, in many foreign countries, English literature begins at early stage of education. The idea of teaching literature at early stage is to make learners familiar with the native culture for linguistic purposes. The aim of this study is to investigate the impact of teaching English literature for EFL (English as a Foreign Language) learners to perform a better performance in English language. In order to improve EFL learners' English proficiency, the researcher advises teachers to create efficient techniques and approaches for teaching English literature.